Impact of Different Diagnostic Criteria on the Reported Prevalence of Junctional Ectopic Tachycardia After Pediatric Cardiac Surgery. Issue 9 (September 2016) - Entenmann, Andreas; Michel, Miriam; Egender, Friedemann; Hessling, Vera; Kramer, Hans-Heiner
Abstract : Objectives: Junctional ectopic tachycardia is a frequent complication after pediatric cardiac surgery. A uniform definition of postoperative junctional ectopic tachycardia has yet to be established in the literature. The objective of this study is to analyze differences in the general and age-related prevalence of postoperative junctional ectopic tachycardia according to different diagnostic definitions. Design: Data files and electrocardiograms of 743 patients (age, 1 d to 17.6 yr) who underwent surgery for congenital heart disease during a 3-year period were reviewed. The prevalence of postoperative junctional ectopic tachycardia in this cohort was determined according to six different definitions identified in the literature and one definition introduced for analytical purposes. Agreement between the definitions was analyzed according to Cohen κ coefficients. A receiver operating characteristic analysis was performed to determine the ability of different definitions to discriminate between patients with increased postoperative morbidity and without. Setting: A university-affiliated tertiary pediatric cardiac PICU. Patients: Infants and children who underwent heart surgery. Interventions: None. Measurements and Main Results: The prevalence of postoperative junctional ectopic tachycardia ranged from 2.0% to 8.3% according to the seven different definitions. Even among definitions for which the general prevalence was almost equal, the distribution according to age varied. Most definitions used a frequency criterion to define postoperative junctional ectopic tachycardia. Definitions based on a fixed frequency criterion did not identify cases of postoperative junctional ectopic tachycardia in patients older than 12 months. The grade of agreement was moderate or poor between definitions using a fixed or dynamic frequency criterion and those not based on a critical heart rate ( κ = 0.37–0.66). In the receiver operating characteristic analysis, the definition with a fixed frequency criterion of 180 beats/min or an age-related frequency criterion according to the 95th percentile showed the optimal cut-off value to determine increased postoperative morbidity. Conclusions: Different definitions of junctional ectopic tachycardia after pediatric cardiac surgery lead to relevant differences in the reported prevalence and age distribution pattern. A uniform definition of postoperative junctional ectopic tachycardia is needed to provide comparable study results and to improve the diagnosis of junctional ectopic tachycardia in pediatric patients. Abstract : Supplemental Digital Content is available in the text.